Development of a copper metabolism-related gene signature in lung adenocarcinoma - Chang, Wuguang; Li, Hongmu; Zhong, Leqi; Zhu, Tengfei; Chang, Zenghao; Ou, Wei; Wang, Siyu (Frontiers in Immunology, 2022)
Purpose The dysregulation of copper metabolism is closely related to the occurrence and progression of cancer. This study aims to investigate the prognostic value of copper metabolism-related genes (CMRGs) in lung adenocarcinoma (LUAD) and its characterization in the tumor microenvironment (TME). Methods The differentially expressed CMRGs were identified in TCGA of LUAD. LASSO and multivariate Cox regression analysis were used to establish the copper metabolism-related gene signature (CMRGS), which was also validated in GEO database (GSE72094). The expression of key genes was verified by qRT-PCR. Then, the CMRGS of LUAD was used to develop a nomogram to predict the 1-, 3-, and 5-year OS. In addition, differences in TMB, biological characteristics and immune cell infiltration between high-risk and low-risk groups were systematically analyzed. Immunophenoscore and IMvigor210 cohort were used to verify whether CMRGs can predict the response to immunotherapy in LUAD. Results 34 differentially expressed CMRGs were identified in the TCGA dataset, 11 of which were associated with OS. The CMRGS composed of 3 key genes (LOXL2, SLC31A2 and SOD3) had showed good clinical value and stratification ability in the prognostic assessment of LUAD patients. The results of qRT-PCR confirmed the expression of key CMRGs in LUAD and normal tissues. Then, all LUAD patients were divided into low/high-risk groups based on median risk score. Those in the low-risk group had a significantly longer OS than those in the high-risk group (P<0.0001). The AUC values of the nomogram at 1, 3, and 5 years were 0.734, 0.735, and 0.720, respectively. Calibration curves comparing predicted and actual OS were close to ideal model, indicating a good consistency between prediction and actual observation. Functional enrichment analysis showed that the low-risk group was enriched in a large number of immune pathways. The results of immune infiltration analysis also confirmed that there were a variety of immune cell infiltration in the low-risk group. In addition, multiple immune checkpoints were highly expressed in the low-risk group and may benefit better from immunotherapy. Conclusion CMRGS is a promising biomarker to assess the prognosis of LUAD patients and may be serve as a guidance on immunotherapy.